Framtidens bränslemix i Härnösand : en jämförelse av HEMAB:s potentiella bränslemixar - Christiansson, Oliver (SLU/Dept. of Energy and Technology, 2021)
Härnösands Energi och Miljö AB (HEMAB) provides district heating in Härnösand and is owned by Härnösand municipality. The fuel mixture of the district heating plant mainly consists of forest residuals, but also some peat. Whether peat is to be considered a fossil fuel or not is debated, however in most cases it is regarded as a fossil fuel. Therefore, HEMAB is interested in evaluating other types of fuel to replace peat, and therefore be able to claim that their district heating is carbon neutral. Peat is however regarded as a good fuel from a combustion perspective, mainly because it contains large amounts of sulphur, which counteracts corrosion inside the combustion chamber. The purpose of this report is therefore to evaluate and compare other types of fuel that can be used instead of peat. The proposed fuel mixtures were compared with respect to their combustion properties, CO2-emissions, and economic aspects. In addition to this a minor analysis of how an increased domestic production of biofuels may affect district heating companies were made. The proposed fuel mixtures are shown below: